Estimating the economic benefits of eliminating job strain as a risk factor for depression. (19th October 2011) - LaMontagne, Anthony; Sanderson, Kristy; Cocker, Fiona
Abstract : Objectives: Building on previously-published population-attributable risk estimates of job strain-attributable (past year) depression of 13.2% for men and 17.2% for women, this study quantified the potential financial benefits of eliminating job strain as a risk factor for depression. Methods: State-transition Markov modelling was used to capture costs and health outcomes from a societal perspective over 1-year and lifetime time horizons. Epidemiologic inputs were sourced from the 2007 Australian National Survey of Mental Health and Wellbeing. Cost inputs were sourced nationally (from Australian national Medicare system) and from the international literature. The analysis was prevalence-based, and modelled the future costs and health outcomes for persons that were employed and met criteria for lifetime DSM-IV major depression in the study reference year (2007). Results: In 2007 the weighted lifetime prevalence of DSM-IV depression in the Australian workforce was 14.7% (12.0% men, 18.0% women). In 1 year, 890 million (5.8%) of the societal cost of depression in the Australian workforce was attributable to job strain. The majority of these costs were incurred by employers, arising from the costs of lost productive time and increased risk of job turnover/job loss among employees with depression. Conclusions: Given that feasible and effective means are available for reducing job strain (as demonstrated in systematic reviews of job stress intervention research), these findings provide a business incentive for expanding psychosocial risk management efforts, complementing and reinforcing legal and ethical directives.